XRD, FTIR and ultrasonic investigations of cadmium lead bismuthate glasses - Amin Abd El-Moneim; M. A. Azooz; Hassan A. Hashem; A. M. Fayad; R. L. Elwan (Scientific Reports, 2023)
Abstract Cadmium lead bismuthate glasses in the system xCdO–(1−x)[0.5PbO + 0.5Bi2O3](40 mol% ≤ x ≤ 90 mol%) were successfully prepared by melt-quenching method. The structural and elastic properties have been investigated using XRD, FTIR and ultrasonic pulse–echo techniques. The XRD patterns confirmed the amorphous nature of the samples prepared. Density and ultrasonic velocity data were used to evaluate various elastic properties. Addition of CdO gave rise to decreased density and molar volume and increased elastic moduli, micro-hardness, and Debye temperature. The FTIR analysis revealed that increasing CdO content enhances the BiO6 octahedral sites at the expense of the BiO3 and PbO4 units. This results in the formation of Pb–O–Bi(6) and Bi(3)–O–Bi(6) linkages in the glass network, which stiffen the structure and improve the elastic properties. A correlation between elastic and compositional parameters was achieved on the basis of theories and approaches in the field.